Adobe Animate CC-Based Flipbook Interactive Media Development IPA Lesson Content - Ulfiya, Firda; Sutaryono, Sutaryono (Elementary School Teacher, 2021)
This study at develop instructional media, test the viability and effectiveness of adobe animate cc based interactiveflipbook media on the force and motion topic for the 4th students at Mranggen 4 Elementary School. The method usedResearch and Development (RD). The results showed that interactive media of adobe animate cc based flipbooks canbe used in learning based on the content expert's assessment with a percentage of 75% in the viable category and 78.12%by media expert in the very viable category. The pretest and posttest learning outcomes calculated using N-Gain increasedby 0.4520 in the moderate category. Based on the hypothesis test with the t-test, the output paired sample test with excelobtained tcount (12,937) ttable (2,045) so Ho was rejected,Keywords: Flipbook interactive media, learning outcomes, natural sciences